PRINCIPLES OF RUSSIAN PUNCTUATION - Aminboeva N. K. (American Journals, 2023)
The ability to interpret the text, as many researchers rightly point out, allows one to join the author's vision of the world, enrich oneself spiritually, and improve the spiritual culture of a person. When analyzing a literary text, the dominant place is usually given to lexical and stylistic means, however, syntactic means, which have come to the fore in modern literature, play a crucial role in creating the expressiveness of the text, in understanding the main idea of the work and the author's worldview. But it should be noted that the problem of punctuation in general linguistics is still waiting for it is solution: there is no single definition of the term "punctuation", there are disputes about the functions it performs, the issue of the leading principle of punctuation has not been resolved.
Keywords: punctuation, punctuation marks, intonation.